Women in the Context of the Drugs:: Social Representations of Users in Treatment - Medeiros, Katruccy Tenório; Maciel, Silvana Carneiro; Sousa, Patrícia Fonseca (Paidéia (Ribeirão Preto), 2018)
Women drug comsumption is a phenomenom influenced by speeches regarding gender relationships and standardizing social structures. This study aims to analyze the representational dimension of female drug users through the social representation theory; it is a qualitative, descriptive field study with 45 women admitted to therapeutic communities and rehabilitation clinics in the states of Paraíba and Pernambuco, Brazil. This study uses a sociodemographic questionnaire and a semi-structured interview, which were submitted to qualitative textual analysis using IRAMUTEQ software. The results indicate that the female drug user is represented as someone who presents a threat and lacks self-control; anchored in representational elements concerning the transgression of social norms, she is considered to have set herself apart from the social roles assigned to women. Such images projected in society and shared by the users affect the manner in which they address chemical dependency and have consequences for their inclusion in their families and society, their expression of identity and the manner in which they perform social roles.